2023
DOI: 10.3390/pharmaceutics15020354
|View full text |Cite
|
Sign up to set email alerts
|

A CO2-Responsive Imidazole-Functionalized Fluorescent Material Mediates Cancer Chemotherapy

Abstract: We present a breakthrough in the synthesis and development of functional gas-responsive materials as highly potent anticancer agents suitable for applications in cancer treatment. Herein, we successfully synthesised a stimuli-responsive multifunctional material (I-R6G) consisting of a carbon dioxide (CO2)-sensitive imidazole moiety and spirolactam-containing conjugated rhodamine 6G (R6G) molecule. The resulting I-R6G is highly hydrophobic and non- or weakly fluorescent. Simple CO2 bubbling treatment induces hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…40−43 Thus, it is reasonable to hypothesize that bubbling CO 2 into an aqueous solution of I-PT might facilitate a rapid reaction between the imidazole side groups of I-PT with CO 2 to form imidazolium salts with a bicarbonate ion, and thereby affect the surface charge and selfassembly properties of I-PT and possibly enhance its fluorescence performance in an aqueous environment. 32,44 As expected, after bubbling CO 2 into 0.1 mg/mL I-PT aqueous solution at 25 °C for 0−600 s, the maximum fluorescence band of I-PT gradually red-shifted from 552 to 563 nm, while the fluorescence intensity also gradually increased from 2800 to 6500 (Figure 2a). This remarkable red shift and greatly enhanced fluorescence intensity may be due to the introduction of a large amount of imidazolium salt into the self-assembled spherical I-PT nanoparticles on CO 2 bubbling, thereby promoting salt-induced phase separation within the nanoparticles, eventually leading to the formation of aggregates that greatly enhance the fluorescence properties of I-PT.…”
Section: ■ Results and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…40−43 Thus, it is reasonable to hypothesize that bubbling CO 2 into an aqueous solution of I-PT might facilitate a rapid reaction between the imidazole side groups of I-PT with CO 2 to form imidazolium salts with a bicarbonate ion, and thereby affect the surface charge and selfassembly properties of I-PT and possibly enhance its fluorescence performance in an aqueous environment. 32,44 As expected, after bubbling CO 2 into 0.1 mg/mL I-PT aqueous solution at 25 °C for 0−600 s, the maximum fluorescence band of I-PT gradually red-shifted from 552 to 563 nm, while the fluorescence intensity also gradually increased from 2800 to 6500 (Figure 2a). This remarkable red shift and greatly enhanced fluorescence intensity may be due to the introduction of a large amount of imidazolium salt into the self-assembled spherical I-PT nanoparticles on CO 2 bubbling, thereby promoting salt-induced phase separation within the nanoparticles, eventually leading to the formation of aggregates that greatly enhance the fluorescence properties of I-PT.…”
Section: ■ Results and Discussionsupporting
confidence: 74%
“…Recent research reported that imidazole and imidazole-derivative materials exhibit specific selectivity and excellent adsorption/desorption characteristics for CO 2 in water or solid-state environments. Thus, it is reasonable to hypothesize that bubbling CO 2 into an aqueous solution of I-PT might facilitate a rapid reaction between the imidazole side groups of I-PT with CO 2 to form imidazolium salts with a bicarbonate ion, and thereby affect the surface charge and self-assembly properties of I-PT and possibly enhance its fluorescence performance in an aqueous environment. , Therefore, the effects of CO 2 bubbling on the fluorescence properties and self-assembly behavior of I-PT in aqueous solution at 25 °C were subsequently explored by PL and DLS. As expected, after bubbling CO 2 into 0.1 mg/mL I-PT aqueous solution at 25 °C for 0–600 s, the maximum fluorescence band of I-PT gradually red-shifted from 552 to 563 nm, while the fluorescence intensity also gradually increased from 2800 to 6500 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…R6G was chosen as a model dye, which radically changes its fluorescence during the transition from an aqueous medium to a hydrophobic one, both the intensity of fluorescence emission and the λ max [ 37 , 38 ]. Therefore, we study the thermograms of gels and monitor the phase transition via the fluorescence of rhodamine 6G, the fluorescence intensity of which increases when interacting with the Chit5-PEG5 polymer at 25–35 °C, and then, with further heating, the fluorescence intensity drops sharply due to the formation of a gel from disordered polymer chains around fluorophore molecules ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of fluorophores for FRET probes is also justified by their potential as potential medicines: Rhodamine 6G and its derivatives [ 11 , 12 ], as well as Coumarin and derivatives, are model cytostatics proposed for use as medicines [ 13 ] and as model fluorophores for studying the loading degree.…”
Section: Introductionmentioning
confidence: 99%